New Miniature Planar Microstrip Antenna Using DGS for ISM Applications - R. Er-rebyiy; J. Zbitou; M. Latrach; A. Tajmouati; A. Errkik; L. EL Abdellaoui (Universitas Ahmad Dahlan, 2017)
The aim of this paper is to use defected ground structures (DGS) in order to miniaturize a microstrip patch antenna. The DGS structure is integrated in the ground plane to improve the performance of the planar antenna, and shifted the resonance frequency from 5.8 GHz to 2.5 GHz, with a miniaturization up to 83%. The antenna is designed, optimized, and miniaturized by using the CST MW-studio, mounted on an FR-4 substrate having a dielectric constant 4.4, a loss tangent tan (ɸ)=0.025, thickness of 1.6 mm with the whole area of 34X34 mm2.The proposed antenna is suitable for ISM (Industrial, Scientific and Medical) applications at 2.5 GHz with S11 ≤(-10) dB. The antenna is fed by 50ohm input impedance and it has good performances in terms of matching input impedance and radiation pattern. The proposed antenna was fabricated and tested.Simulation and measurement results are in good agreement.